Altering the Order of Public Worship - Herron, Andrew (Scottish journal of theology, 1951)
It is commonly accepted as a basic principle of Presbyterianism that the conduct of public worship belongs exclusively to the Minister under authority of the Presbytery. Strictly speaking the position is that matters entering into the actual performance of public worship or the administering of ordinances are the business of the Presbytery and the Minister is recognised as the executive officer of the Presbytery. What this amounts to in all ordinary cases is that there is vested in the Minister the entire responsibility for the ordering of the Service—a very grave responsibility indeed.